(untitled) (Research, Society and Development, 2021)
This study aimed to identify the conditions, expectations, and capacities of professors from face-to-face courses (technical and higher education) to carry out remote teaching activities mediated by digital technologies, due to the COVID-19 pandemic and the social distancing measures. Exploratory and quantitative research was developed, with a convenience non-probabilistic sample of 588 Brazilian professors from public and private educational institutions. Participants were invited by social networks to complete voluntarily an online questionnaire, between June 19 and 30, 2020. Descriptive statistical analyses were performed (e.g., frequency, mean, standard deviation), as well as inferential analyses, for example, exploratory factor analysis and multiple linear regressions. The results highlight that the majority of the investigated professors showed a predisposition and interest in performing remote teaching activities, in addition to technical conditions for accessing and using the internet and digital and computational equipment. Despite this, school institutions need to pay attention to the factors associated with the home environment, such as domestic and family demands and the individual needs who can become barriers to the effective development of Emergency Remote Education.